Microglia-associated research in Parkinson’s disease: a bibliometric analysis - Chen, Yan-Jun; Xie, Ming-Rong; Zhou, Sheng-Qiang; Liu, Fang (Frontiers in Aging Neuroscience, 2025)
BackgroundParkinson’s disease (PD) is a neurodegenerative disorder that predominantly affects the elderly. Evidence indicates that microglia-mediated neuroinflammation is recognized as one of the key mechanisms in PD. This study aims to analyze the key points, hotspots, and emerging frontiers in research related to PD and microglia.MethodPublications were obtained from the Web of Science and PubMed databases. VOSviewer and CiteSpace were used to generate visual representations and conduct numerical analyses of the dataset.ResultsChina and the United States were the leading contributors. Shanghai Jiao Tong University was the most active institution. The Journal of Neuroinflammation published the most papers on microglia and PD. Dr. Jau-Shyong Hong was the most prolific author. High-frequency keywords included PD, microglia, neuroinflammation, alpha-synuclein (a-syn), neurodegeneration, microglial activation, and oxidative stress. Gut microbiota and the NLRP3 inflammasome have garnered significant interest from researchers in recent years.ConclusionThis study generated visual mappings of microglia and PD-related research. Neuroinflammation, a-syn, neurodegeneration, microglial activation, and oxidative stress represent major focuses and hotspots in this field. Gut microbiota and the NLRP3 inflammasome have rapidly attracted research attention and are likely to be key directions for future studies in the coming years.